PENGARUH ANTARA LUAS PANEN DAN PRODUKTIVITAS TERHADAP PRODUKSI JAGUNG DI WILAYAH INDONESIA PADA TAHUN 2023 - Syafitri, Fatika; Arifudin, Arifudin; Faradilah, Deviyanti (Universitas Jambi, 2024)
Corn is a strategic commodity that can be used as a substitute for rice, therefore, corn production requires serious attention in efforts to support national food security. Harvested area and productivity are two key factors influencing corn production levels. Therefore, accurate analysis is needed to determine the extent to which these two factors impact corn production in an effort to strengthen food security. This study aims to analyze the influence of harvested area and productivity on corn production in various provinces in Indonesia in 2023. The method used is panel regression analysis, which allows testing the influence of independent variables (harvested area and productivity) on the dependent variable (corn production) by considering both time and regional dimensions. The results show that harvested area and productivity have a significant effect on corn production at the provincial level. Provinces with high harvested area and productivity tend to have greater corn production. However, there is variation between provinces due to differences in climate conditions and other factors. These findings have important implications for the planning and development of the corn agricultural sector, where targeted increases in harvested area and productivity can support increased national corn production. However, such improvement strategies need to be tailored to the characteristics of each region.